2017
DOI: 10.1016/j.jhydrol.2017.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Reactive transport modelling to infer changes in soil hydraulic properties induced by non-conventional water irrigation

Abstract: The use of non-conventional water (e.g., treated wastewater, desalinated water) for different purposes is increasing in many water scarce regions of the world. Its use for irrigation may have potential drawbacks, because of mineral dissolution/precipitation processes, such as changes in soil physical and hydraulic properties (e.g., porosity, permeability), modifying infiltration and aquifer recharge processes or blocking root growth. Prediction of soil and groundwater impacts is essential for achieving sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…Flow through porous media is ubiquitous in many natural and industrial systems. Examples include flow through biological tissues, blood vessels and bones [1][2][3] or through soils, sediments and rocks, with long-standing interest in hydrology [4,5], petroleum [6], and chemical engineering [7][8][9]. At low Reynolds numbers (Re≪1) the bulk flow of a Newtonian fluid flowing through porous media is described by Darcy's law…”
Section: Introductionmentioning
confidence: 99%
“…Flow through porous media is ubiquitous in many natural and industrial systems. Examples include flow through biological tissues, blood vessels and bones [1][2][3] or through soils, sediments and rocks, with long-standing interest in hydrology [4,5], petroleum [6], and chemical engineering [7][8][9]. At low Reynolds numbers (Re≪1) the bulk flow of a Newtonian fluid flowing through porous media is described by Darcy's law…”
Section: Introductionmentioning
confidence: 99%
“…Clay mineral content (illite) in Layer 1 accounted for up to 9.7% and was practically absent in Layer 2 (Table 2). Detailed site descriptions can be found in previous studies (Valdes‐Abellan et al, 2015, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The salinity difference between deionized water in the vapor chamber and water in the soil would explain this process. Long‐term irrigation with brackish water could lead to accumulation of salts, and in Valdes‐Abellan et al (2017) gypsum was identified as the main mineral to precipitate in the soil. The impact on soil hydrophilic behavior depends on the type of salts present in the system, which depends on the soil mineralogy and the chemistry of the applied irrigation water.…”
Section: Discussionmentioning
confidence: 99%
“…Valdes-Abellan et al (2017) developed a model (using HP1) to simulate the spatial-temporal evolution of soil hydraulic properties during non-conventional water irrigation during non-isothermal transient flow. In addition to linking the porosity, a h , and the saturated hydraulic conductivity to the amount of precipitated or dissolved minerals, soil hydraulic properties were also linked to changes in the soil water composition, salinity, and temperature.…”
Section: Overview Of Recent Applicationsmentioning
confidence: 99%